KARAKTERISTIK MANUSIA DALAM PERSPEKTIF AL-QUR’AN - Mhd. Idris dan Desri Ari Enghariano (Al FAWATIH:Jurnal Kajian Al Quran dan Hadis, 2020)
Humans are one of the main actors in the Qur'an. Many verses of the Al-Qurʻan discuss about humans both their strengths and weaknesses. For this reason, this article aims to study the classification of terms related to humans in the Qur'an, the strengths and weaknesses of humans according to the Qur'an perspective. This study uses the method of tafsir maudhu'i (thematic interpretation). The results showed that the classification of terms that are often mentioned in the Qur'an about humans are; al-basyar, al-insan, al-naas, the children of Adam, and zuriyat Adam. In addition, other terms are also added to humans, such as: ‘Abdullah and the Khalifah. Among the advantages possessed by humans according to the Qur'an lies in physical, mind and heart. As for the human shortcomings according to the al-Qur`an, among others: like to complain and miserly, weak nature, wrongdoing and stupid, arguing and like to argue, hopeless and ungrateful, in a hurry, sinner, hesitant about the day of retribution.